Group Guidance Service: Discrepancies Between Standard and Actual Practice - Dian Ari Widyastuti; Edi Purwanta; Budi Astuti (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
Group guidance services play a crucial role in developing students' potential, but their implementation often fails to conform to established standards. This study aims to evaluate the gap between the standards and actual practices of group guidance services in private junior high schools in Yogyakarta City. Using a mixed-methods approach with a discrepancy model, the study involved ten BK teachers who were selected through purposive sampling techniques. Data were collected through evaluation questionnaires and in-depth interviews, and then analyzed using descriptive statistics and content analysis. The results showed that most BK teachers did not regularly carry out services and that these services were not based on a systematic needs assessment. Key findings suggest that structural barriers such as administrative burdens and the absence of schedules remain key factors. Recommendations include the need for needs assessment training, innovative service strategies, and the regular inclusion of special hours for BK services in the school curriculum. Keywords: discrepancy model, guidance and counseling teacher, group guidance service